A novel natural GRAS-grade enteric coating for pharmaceutical and nutraceutical products - Khoder, Mouhamad; Schropp, Verena; Zeitler, Susanne; Pereira, Beatriz; Habashy, Rober; Royall, Paul G.; Wang, Julie Tzu Wen; Alhnan, Mohamed A. (International Journal of Pharmaceutics, 2020)
In this study, enteric coatings based exclusively on naturally occurring ingredients were reported. Alginate (Alg) and pectin (Pec) blends with or without naturally occurring glyceride, glycerol monostearate (GMS), were initially used to produce solvent-casted films. Incorporating GMS in the natural polymeric films significantly enhanced the acid-resistance properties in gastric medium. Theophylline tablets coated with Alg-Pec blends without GMS disintegrated shortly after incubation in gastric medium (pH 1.2), leading to a premature and complete release of theophylline. Interestingly, tablets coated with Alg-Pec blends that contain the natural glyceride (GMS) resisted the gastric environment for 2 h with minimal drug release (<5%) and disintegrated rapidly following introduction to the intestinal medium, allowing a fast and complete drug release. Furthermore, the coating system proved to be stable for six months under accelerated conditions. These findings are particularly appealing to nutraceutical industry as they provide the foundation to produce naturally-occurring GRAS based enteric coatings.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Code oil; Delayed-release; Enteric-coatings; Gastro-resistant; Nutraceuticals; Probiotics